2019
DOI: 10.1021/acs.nanolett.8b04729
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Prussian Blue Nanozymes Drive Neuroprotection against Ischemic Stroke via Attenuating Oxidative Stress, Counteracting Inflammation, and Suppressing Cell Apoptosis

Abstract: Ischemic stroke is a devastating disease and one of the leading causes of mortality worldwide. Overproduction of reactive oxygen and nitrogen species (RONS) following ischemic insult is known as a key factor in exacerbating brain damage. Thus, RONS scavengers that can block excessive production of RONS have great therapeutic potential. Herein, we propose an efficient treatment strategy in which an artificial nanozyme with multienzyme activity drives neuroprotection against ischemic stroke primarily by scavengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
188
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(222 citation statements)
references
References 73 publications
3
188
0
Order By: Relevance
“…Neuroinflammation is an important and harmful mechanism in cerebral ischemia-reperfusion injury [49,50]. It has been reported that the TLR4/NF-κB signaling pathway and the TLR4/MAPK signaling pathway has an important relationship with neuroinflammation in the MCAO/R model, which have the similar molecular mechanisms as the LPS-activated expression of proinflammatory factors in microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation is an important and harmful mechanism in cerebral ischemia-reperfusion injury [49,50]. It has been reported that the TLR4/NF-κB signaling pathway and the TLR4/MAPK signaling pathway has an important relationship with neuroinflammation in the MCAO/R model, which have the similar molecular mechanisms as the LPS-activated expression of proinflammatory factors in microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke occurs when the blood flow to a certain portion of the brain is obstructed secondary to occlusion of cerebral arteries. The following deprivation of oxygen and energy triggers an ischemic cascade, such as OS and inflammation, resulting in neuronal excitotoxicity and cell death ( Khoshnam et al, 2017 ; Li et al, 2019a ; Zhang K. et al, 2019 ). Before ferroptosis was defined, iron accumulation [for review see Selim and Ratan (2004) ] had been found in lesioned regions, such as the basal ganglia and the hippocampal area of the brain, and iron overload exaggerated neuronal damage during reperfusion ( Dietrich and Bradley, 1988 ; Kondo et al, 1995 ; Lipscomb et al, 1998 ; Park et al, 2011 ).…”
Section: The Role and Mechanism Of Ferroptosis In Acute Cns Injuriesmentioning
confidence: 99%
“…Prussian blue nanozymes (HPBZs) possessed multienzyme activity assisted with Bi3 + and exerted antiapoptotic effects to protect cells from ischemia-induced injury by regulating the expression of anti-and pro-apoptotic proteins in vitro and vivo in a recent study [45]. Although the material structure of HPBZs did a little differ from PBNPs, the anti-apoptotic effects may be closely related to ROS scavenging.…”
Section: Discussionmentioning
confidence: 99%